Influência do habitat e da disponibilidade de substrato vegetal na sobrevivência, crescimento e densidade de colônias da saúva Atta laevigata (Fr. Smith) em uma área de cerrado - Vieira Neto, Ernane Henrique Monteiro (2008)
Generalist herbivores usually increase in abundance in disturbed habitats. However, the mechanisms driving this expansion are poorly known. In this study I tested the effects of habitat and availability of food resources on a keystone herbivore in Neotropical savannas, the leaf-cutter ant Atta laevigata. Through experimental transplants among habitats (dirt roads and vegetation) and supplementation of food (with and without), I determined the importance of these factors to the survival, growth and density of ant-colonies during different life-stages. Furthermore, I monitored an ant population for three years and related habitat parameters to the abundance of ant-colonies. My results showed that the survivorship during the claustral phase was significantly higher in dirt roads and in areas with a sparser tree cover. In addition, 3-month old colonies (incipient phase) were limited by habitat (greater survival in dirt roads) and by food availability (greater survival and growth of supplemented colonies). However, the habitat effect disappeared in 15-month old colonies (young phase); only food availability resulted in greater survival and growth of these colonies. Finally, population structure was similar among the study years, and the greater density of small colonies was related to lower tree-cover, litter-cover and greater proximity to dirt roads, while density of big colonies was not related to any of these parameters. The results indicate that the selection of roads as preferred nesting sites by Atta queens increase the fitness of the colony as a result of the increased survival during initial life-stages (claustral and incipient phases). Thus, the increased abundance of Atta in disturbed habitats is probably a result of the increased survival at early life-stages due to better microclimate and the release of food limitation in these habitats.